Analisis Kausalitas Teknologi Informasi Dan Komunikasi, Konsumsi Listrik Dan Pertumbuhan Ekonomi Di Indonesia - Desi Rahmadani Putri; Ariusni Ariusni (Universitas Negeri Padang, 2022)
This study aims to see and analyze the causality of Information and Communication Technology, Electricity Consumption and Economic Growth in Indonesia. This research is included in descriptive and associative research which explains whether or not causality between research variables. The data used are secondary data and panel data from 2015-2019, which consists of 34 provinces in Indonesia. The analysis used in this research is Vector Auto Regression (VAR) analysis. The results of this study found that (1), information and communication technology has no unidirectional or bidirectional influence on electricity consumption in Indonesia, (2) information and communication technology has a one-way causal effect on economic growth in Indonesia, (3) electricity consumption does not have a unidirectional or bidirectional causality effect on economic growth in Indonesia.